Implementasi Pembelajaran Kitab Akhlaq Lil Banin dalam Pembentukan Akhlaq Santri di Pondok Pesantren Al-Qur’an Babussalam Kabupaten Bandung - Kaefah Arini; Aep Saepudin; Helmi Aziz (UNISBA Press, 2022)
Abstract. This studied aims to find out how the application of learning the book of Akhlaq Lil Banin in the Formation of Santri Morals was carried out at the Al-Qur’an Babussalam Islamic Boarding School in Bandung Regency, with the focus of research covering 1) Planning for learning the book of Akhlaq Lil Banin in Formation of Santri Morals, 2) Implementation learning the book of Akhlaq Lil Banin in the Formation of Santri Morals, and 3) Evaluating the book of Akhlaq Lil Banin in the Formation of Santri Morals.The approached in this studied uses a qualitative approached, while the type of research used in this studied is descriptive qualitative. Data collection techniques using interviews, observation and documentation. Data analysis techniques include data reduction, data presentation and drawing conclusions. Checking the validity of the findings is done by triangulation technique. The results showed that: 1) Planning for learning the book of Akhlaq Lil Banin is completely left to the teachers by paying attention to several aspects such as objectives, methods, media and learning delivery strategies that are suitable for learning the book of Akhlaq Lil Banin 2) The implementation of this book learning is carried out once a week, namely on Wednesdays at 19.30-20.30 WIB and takes place at the Ta'lim Council. And so far in the implementation of each student always plays an active role in learning. 3) Evaluation of learning the book of Akhlaq Lil Banin at Al-Qur’an Babussalam Islamic Boarding School Bandung Regency using evaluation of test techniques and non-test techniques. Abstrak. Pokok bahasan dalam penelitian ini bertujuan untuk mengetahui bagaimana penerapan pembelajaran kitab Akhlaq Lil Banin dalam Pembentukan Akhlaq Santri yang dilaksanakan di Pondok Pesantren Al-Qur’an Babussalam Kabupaten Bandung, dengan fokus penelitian mencakup 1) Perencanaan pembelajaran kitab Akhlaq Lil Banin dalam Pembentukan Akhlaq Santri, 2) Pelaksanaan pembelajaran kitab Akhlaq Lil Banin dalam Pembentukan Akhlaq Santri, dan 3) Evaluasi pembelajaran kitab Akhlaq Lil Banin dalam Pembentukan Akhlaq Santri. Pendekatan dalam penelitian ini menggunakan pendekatan kualitatif, dengan metode deskriptif analisis. Teknik pengumpulan data dengan menggunakan wawancara, observasi dan dokumentasi. Teknik analisis data meliputi reduksi data, penyajian data dan penarikan kesimpulan. Pengecekan keabsahan temuan dilakukan dengan teknik triangulasi. Hasil penelitian menunjukan bahwa: 1) Perencanaan pembelajaran kitab Akhlaq Lil Banin diserahkan sepenuhnya kepada ustadz-ustadzah dengan memperhatikan beberapa aspek seperti tujuan, metode, media dan strategi penyampaian pembelajaran 2) Pelaksanaan pembelajaran kitab ini dilakukan sekali dalam sepekan yaitu pada hari Rabu Pukul 19.30-20.30 WIB dan bertempat di Majelis Ta’lim (MT). 3) Evaluasi pembelajaran kitab Akhlaq Lil Banin di Pondok Pesantren Al-Qur’an Babussalam Kabupaten Bandung menggunakan evaluasi teknik tes dan teknik non tes.